Neuromyelitis Optica: A Case Report - Utku, Uygar; Dinç, Aytaç; Gökçe, Mustafa (European Journal of Therapeutics, 2010)
Neuromyelitis optica (Devic's disease) is an idiopathic inflammatory demyelinating disease of central nervous system that preferentially affects the optic nerve and spinal cord. Although neuromyelitis optica had long been thought of as a variant of multiple sclerosis, it was understood as a different entity. A 28 year old woman presented with urinary and fecal incontinence and numbness on her arms and legs. Neuromyelitis optica was diagnosed according to her clinic and laboratory findings. It is important to distinguish between multiple sclerosis and neuromyelitis optica because they have different management.